Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1998
DOI: 10.1128/jvi.72.11.9278-9285.1998
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Organization of the Avian Adenovirus CELO

Abstract: A detailed map of the transcriptional organization of the CELO virus genome was produced. Recent computer analysis of CELO virus has indicated the presence of 38 putative open reading frames (ORFs). This study, based on analysis of the transcriptional products of CELO in vitro, confirmed the presence of RNAs for 26 of these 38 ORFs. All of the results were obtained by cDNA isolation or specific reverse transcriptase PCR. Observation of ORF transcription kinetics postinfection revealed the existence of early an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

1999
1999
2006
2006

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 53 publications
0
12
0
Order By: Relevance
“…Initial studies on the sequential appearance of CELO virus transcripts revealed that Orf22 transcripts are detectable 2 h p.i. and therefore belong to the early transcription units (42), a feature shared with human adenovirus E1A. These RNA data have been confirmed by Western blotting with serum raised against the Orf22 protein.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…Initial studies on the sequential appearance of CELO virus transcripts revealed that Orf22 transcripts are detectable 2 h p.i. and therefore belong to the early transcription units (42), a feature shared with human adenovirus E1A. These RNA data have been confirmed by Western blotting with serum raised against the Orf22 protein.…”
Section: Discussionmentioning
confidence: 53%
“…These data classify Orf22 as an early transcription product, a result that is supported by studies on CELO virus RNA products where Orf22 transcripts were detectable from 2 h p.i. (42).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The determination of transcription maps for some xenogenic viruses has assisted vector design by complementing the data on genome structure. The major transcription units have been described for BAdV3 and PAdV3 [24,46,71], FAdVl [84] and OAdV7 [72]. No transcription map has been reported for CAdV2.…”
Section: Transcription Mapsmentioning
confidence: 99%
“…Studies of FAdVl identified many transcripts for ORFs in the genome and a major transcription unit that is controlled by the MLP. However, at the left and right ends of the genome there are 5 and 15 kb, respectively, for which the promoters and transcriptional organization is undefined [84]. In the OAdV7 genome, the left (LHl to LH3)-and right-hand ends (RHl to RH6), E2 and the proposed E4 region (E4.1 to E4.3), as well as the structural protein genes constitute individual transcription units.…”
Section: Transcription Mapsmentioning
confidence: 99%